ChemInform Abstract: Cobalt Mediated C‐H Bond Functionalization: Emerging Tools for Organic Synthesis. Issue 40 (30th September 2014) - Tilly, David; Dayaker, Gandrath; Bachu, Prabhakar
Abstract Review: 170 refs.